Problems and challenges of solid waste management: a case study in South Johor, Malaysia - Salim, Mohd. Razman (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 1994)
Many urban areas in Malaysia are experiencing waste management problems due to the enhancement of urbanization and industrialization. These are further escalated by urban growth, changing consumption habits as well as social lifestyles. This new growth has been accompanied with an ever increasing rural-urban migration which culminates in the proliferation of squatter areas due to the scarcity of land and resources. The increase has given rise to collection and disposal problems which could pose as a potential environmental pollution and health risk to the general public through disease transmission. In this paper, the impact of solid waste management to the environment will be evaluated. It is also aim at introducing to the public the awareness of the health and safety risks caused by solid waste.